Service user involvement : reaching the hard to reach in supported housing - Brafield, Helen, 1966- (Jessica Kingsley Publishers, 2008)
Drawing on extensive research, this book offers imaginative and effective strategies for consultation with service users who have been historically difficult to engage with, including homeless people, care leavers, ex-offenders, travellers, women escaping domestic violence and black and minority ethnic groups.